Asbestos in Colombia: A silent enemy = Asbesto en Colombia: un enemigo silencioso - Ossa Giraldo, Ana Claudia (Iatreia, 2014)
Asbestos is a group of fibrous non-metallic minerals, composed of double chain silicates, that shows high resistance to tension and chemical degradation and low thermal conductivity. Despite being recognized as carcinogenic agents by the World Health Organization (WHO), based on experimental evidences and population studies, asbestos are still used in many countries at the expense of the health of workers. This has become a worldwide problem associated with the increase of asbestos-related diseases in exposed persons. In this article, we review asbestos and their associated diseases; the use, exposure and existing regulations on asbestos both in Colombia and in other countries. Finally, we raise the possibility of evaluating the usefulness of genetic monitoring in addition to following-up exposed individuals. This would enable a better surveillance in our country with respect to lung cancer, mesothelioma and other asbestos-related diseases.